The Role of The Ministry of National Development Planning of The Republic of Indonesia in Public-Private Partnership - Paramita, Aulia Annisa; Purwanti, Nurul Dwi (PT Penjaminan Infrastruktur Indonesia (Persero), 2023)
This study addresses the notable gap in existing research by examining the critical role of The Ministry of National Development Planning/National Development Planning Agency (Kementerian PPN/Bappenas) in the country’s infrastructure development through Public-Private Partnerships (PPP) financing scheme. Utilizing qualitative methods, the research identifies three key dimensions of Bappenas’ role in PPP: Government Policy and Political Commitment, Legal and Regulatory Framework, and PPP Supporting Bodies. These dimensions encompass five primary roles—Provider, Regulator, Coordinator, Supervisor, and Project Participant. The study also reveals significant challenges, with out-of-control risks such as unpredictable pandemics posing a major hindrance. To address these issues, the research recommends The Ministry of National Development Planning/ National Development Planning Agency (Kementerian PPN/Bappenas) to develop comprehensive regulations and conduct ongoing capacity building to enhance stakeholders’ PPP knowledge and address the capacity of human resources within the Government Contracting Agency (GCA). In addition, encourage policymakers to shift their mindset, advocating for early integration of PPPs as the primary funding mechanism in infrastructure projects, boosting feasibility and success.